2004
DOI: 10.1534/genetics.166.3.1385
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Segregation Analysis of Deafness in U.S. Dalmatians

Abstract: Hereditary loss of hearing affects many breeds of the domestic dog, but the Dalmatian has the highest prevalence. Approximately 30% are affected in the United States (U.S.) population. It is widely accepted that a relationship exists between deafness and pigmentation in the dog and also in other animals. While the Dalmatian exemplifies this relationship, the genetic origin and mode of inheritance of deafness in this breed are unknown. The goals of this study were to: (1) estimate the heritability of deafness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 28 publications
3
56
1
Order By: Relevance
“…25 Several studies have demonstrated that congenital deafness is inherited in Dalmatians, but the exact mechanism is controversial. 9,23 Neither a dominant nor a recessive simple Mendelian mode of transmission could be proven by pedigree analysis. 9,23 Other hypotheses on inheritance have included a model of 2 interacting recessive loci with incomplete penetrance 5 and polygenic determination.…”
Section: Association With Parental Hearing Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Several studies have demonstrated that congenital deafness is inherited in Dalmatians, but the exact mechanism is controversial. 9,23 Neither a dominant nor a recessive simple Mendelian mode of transmission could be proven by pedigree analysis. 9,23 Other hypotheses on inheritance have included a model of 2 interacting recessive loci with incomplete penetrance 5 and polygenic determination.…”
Section: Association With Parental Hearing Statusmentioning
confidence: 99%
“…[3][4][5][6][7][8] Dogs who are deaf by this age are considered to be affected with congenital sensorineural deafness. 1,4,6,7 Although most studies of congenital deafness have formerly been carried out on the Dalmatian, 5,[8][9][10][11][12][13][14][15][16][17] the prevalence of congenital deafness in the Bull Terrier, English Setter, Pointer, Catahoula Leopard dog, Whippet, Australian Cattle dog, Jack Russell Terrier, Dachshund, and English Cocker Spaniel has also been evaluated. 5,[17][18][19] In fact, more than 60 breeds of dog have now been identified as suffering from congenital sensorineural deafness, 17 including the Border Collie.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence none of the results from our study could be compared with the literature, except for polygenic parameters for osteochondrosis (e.g., Kadarmideen et al 2004). In addition, only a few studies have investigated complex segregation analysis for ordinal or binary data (e.g., Thaller et al 1996;Cargill et al 2004) but this is the first study to extensively investigate a liability or threshold model method for identifying major genes for binary diseases in complex pedigrees with inbreeding and marriage loops. The basic theory and algorithms developed in this study could also be used in humans and companion animals (e.g., horses, cats, and dogs) where (poly-or oligogenic) diseases/disorders are observed in categorical form.…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding and marriage loops in a typical segregation analysis using pedigreed populations make the exact computations of likelihoods or marginal densities impossible. This problem has been overcome by the development of a Bayesian method implemented via Gibbs sampling, a Monte Carlo Markov chain (MCMC) methodology (Guo and Thompson 1992), and the application of this methodology to livestock populations ( Janss et al 1997;Hagger et al 2004;Ilahi and Kadarmideen 2004) as well as to companion animals (Cargill et al 2004). 1 No investigations have been carried out so far to determine the mode of inheritance of osteochondrosis in animals (in particular, pigs) by a complex segregation analysis.…”
mentioning
confidence: 99%